A CULTURAL VALUE IN THE MOVIE MIRACLE IN CELL N0.7 BY LEE-HWANKYUNG - Kristiani Fatika Sari; Ch. Evy Tri Widyahening (English Education Department Slamet Riyadi University Surakarta, 2023)
This study aims to analyze the cultural value in the movie entitled Miracle in Cell No.7. The researcher used qualitative method. Reading the script, watching the movie, and note taking record all data movie were the data collected by the researcher. The researcher used the data triangulation and theory triangulation to check validation. The result of the research showed that the cultural values could be found in the movie Miracle in Cell No.7, such as social value as one of component of cultural value there were culture identity and the role of culture in society . Key words : Cultural value, Miracle in Cell No.7 Movie, Qualitative Research